Dari Timur Tengah Ke Bumi Peritiwi Awal Mula Masuknya Islam Ke Nusantara - Melisa Nur Azizah; Rumsinah Rumsinah; Salsabila Alifiya; Ahmad Maftuh Sujana (Reflection : Islamic Education Journal, 2025)
The entry of Islam into the archipelago is a historical process that takes place peacefully and culturally. The role of scholars is the main key in disseminating Islamic teachings through trade, educational, and socio-cultural approaches. Not only preaching, the scholars also mingle with the local community through marriage and the establishment of educational institutions such as Islamic boarding schools. A persuasive and accommodating da'wah strategy for local culture is the main factor in the success of Islamization in various regions. In addition to religious aspects, Islam also has influence in the field of politics and government, both in the application of sharia values, morals, and the formation of Islamic political organizations. Through the study of literature and historical sources, this study shows that the process of spreading Islam in the archipelago is not forceful, but through the harmonious integration of values and culture.